Sistem Informasi Geografis Dalam Pemetaan Lahan Gambut di Kabupaten Musi Banyuasin - Alek Wijaya; Eka Puji Agustini; Eko Nardo (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Conservation of nature is a central issue at this time, this is caused by the increasing number of natural damages that occur because of human ignorance to keep the nature of the world remains a friendly place for our lives. One of the important factor of nature conservation is the sustainability of peatlands which is capable of storing carbon gases that serve to withstand the rate of earth temperature rise. One of the efforts undertaken to maintain the sustainability of peatlands is the availability of the lastest and comprehensive data and information about peatland conditions that can be accessed by stakeholders that related to peatland conditions. For that reason, we need a Geographic Information System that is designed and built using the Classic Life Cycle Model approach and supported by ArcGIS software, UML Model and PHP programming language. Geographic information system provides peatland mapping information such as: location of peatlands, peatland categories, peatlands category that already managed and peatland category not yet managed.